Shari'ah Compliant Private Equity and Islamic Venture Capital. - Farid, Fara Madehah Ahmad (Edinburgh guides to Islamic finance., 2012)
The first guide to the application and operation of Shari'ah -based structures and Islamic venture capital. These case studies and examples of business financial appraisals give an in-depth view of areas including: the Islamic banking industry; its use as a source of funding in the biotechnology industry, pharmaceuticals, ICT, agriculture and fisheries; and how it is used by investment companies as part of their asset management strategies. Key features: Combines theory and practice to build a complete picture of the field.; Gives an overview of the industry before focusing on key areas within.